Sustainagility model and its effects on the Malaysian Palm Oil Plantation Sector - Mukherjee, Aroop (2019)
There has been a growing concern about food production vis-à-vis rising global population and promoting greater sustainability across the complete supply chain. From the published reports, previous research papers, and discussions with the experts of the Malaysian Palm Oil Plantations Sectors (MPOPS), it was noted that sustainability and agility are an important aspect for the MPOPS. The MPOPS faces challenges in terms of fluctuation in the overall yields, rising costs in terms of production, processing of crude oil, sustaining existing position with improvement in position in the world market, and Round Table Sustainable Palm Oil (RSPO)/Malaysia Sustainable Palm Oil (MSPO) certification process. Therefore, the objective of this study was to investigate the effects of sustainagility model in the Malaysian palm oil plantations sector. The study was divided into three phases. The first two phases were integrated into two rounds, namely discussions with the experts and the development of questionnaire items for the Malaysian palm oil plantations as Delphi Technique rounds. A comprehensive review of the responses received was undertaken along with discussions with the experts, which highlighted the attributes and sub-attributes of the model. The third phase of the study entailed triangulation techniques where the primary data were collected through the structured questionnaires prepared during the first and second phases which the questionnaires were given to the plantation managers and mill managers for the quantitative approach. For the qualitative approach, face-toface interviews with three (3) top level management were conducted while 151 samples were collected from the lower and middle level managers supported the quantitative approach. Based on the aforementioned study, the factors were determined and used to further investigate the Malaysian palm oil plantations to be sustainagile. The index was calculated and it was observed that the plantations is slightly highly agile, highly sustainable, and slightly highly sustainagile. The result also suggested that the implementation of agility and sustainability influence the organization to be sustainagile. The results revealed that there is a positive relationship between the flexibility and sustainagility and partially mediated between the agility, sustainability, and sustainagility that enhance the organisation performance and improve its competitiveness by understanding the capabilities. Further, the results reflected that techno-organisation dynamisms act as a quasi moderator in the model that have changed the form of relationship between the flexibility and sustainagility. Hence, for the Malaysian palm oil plantations sector to be sustainagile, technoorganisation dynamism shall play a vital role. Further, the score table and matrix created will help the organisations to verify where they stand in the sustainagility index and enhance its competitiveness, improvise process innovation, attain certification, flexibility, and provide a better learning process for the employees to be sustainagile, so as to handle any radical changes within the organization.